Prophylaxis of Acute Enteric Infections and Viral Hepatitis A under Emergency Situation in the Territory of the Amur Region - T. V. Korita; G. G. Onishchenko; O. P. Kurganova; O. E. Trotsenko; A. A. Perepelitsa (Проблемы особо опасных инфекций, 2014)
Hydrological natural disasters and post-flooding epidemiological situation are often attended by epidemic emergencies creating a threat to life-comforts sustaining and sanitary-epidemiologic welfare of a significant number of citizens. To evaluate the efficiency of preventive and anti-epidemic measures the analysis of acute enteric infection incidence rate in the Amur Region for the past decade, during the high water and in the post-flooding period in 2013 has been carried out. Displayed are the data concerning the prophylaxis of acute enteric infections and viral hepatitis A under the conditions of the emergency situation caused by natural calamities notably by flood in the Amur Region. Adequate planning and operative implementation of organizational, preventive and anti-epidemic measures have made it possible to control acute enteric and viral hepatitis A infection at the sporadic level.